The impact of commodity price shocks on banking system stability in developing countries - Nicholas Ngepah; Margarida Liandra Andrade da Silva; Charles Shaaba Saba (Economies, 2022)
This study examines the impact of commodity price shocks on the banking sector stability of 18 African commodity-exporting economies using an unbalanced panel dataset spanning a 16-year period from 2000-2015. The study on the impact of commodity price shocks on African commodity-exporting economies' banking sectors was estimated using a panel fixed effects model. The empirical findings indicate that commodity price shocks increase bank credit risk (non-performing loans) and, thus, pose a risk to the banking sector stability of African commodity-exporting economies. The results for the disaggregated shocks reveal that both positive and negative shocks weaken banking sector stability. In addition, commodity price shocks are discovered to decrease credit extension to the private sector, highlighting an additional channel through which the impact of commodity price shocks may be perpetuated to the real economy.
Keywords: 330; Africa; banking sector stability; commodity price shocks; panel data